Theoretical Refrigeration Cycle Analysis of HFC125/HCs Binary Mixtures - 胡芃; 赵涛; 陈则韶 (Zhileng xuebao)
HFC125/HCs binary mixtures were proposed to be substitute refrigerants. Based on the NIST REFPROP Database, the performances of the theoretical refrigeration cycle were calculated in and analyzed. The COP of the mixture with optimal composition is about 16.9% higher than that of HCFC22 in theory,and the discharge temperature of compressor is lower.